Investigation of Paternally Inherited Allele Mutation at Short Tandem Repeat (STR) Locus D7S820 Leading to Parent-Child Mismatch - Abdul Hameed; Hafsah Muhammad; Muhammad Ajmal; Siddique, Nayyer (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2024)
During paternity investigation with Identifiler™ set of autosomal Short Tandem Repeats (STRs), a genetic mismatch was observed with D7S820 between the disputed father and child. The genotype at this locus in the disputed father, mother and child was 10/10, 11/12 and 11/11, respectively. The combined paternity index and probability of paternity after including the mutation in the calculation were 7.6×107 and 0.9998, respectively. Both values supported the suspicious father as the biological father of the child. Further analysis of Y-STRs revealed matching of all the alleles of the child with that of the suspicious father. It suggested that the mismatch at the D7S820 locus might be a case of mutation. DNA sequencing of D7S820 PCR products of the child and both the parents helped in determining that the child inherited the expanded repeat of the paternal allele 10, which was transmitted as allele 11 in the child from the suspicious father.